Jogos educativos como ferramenta de aprendizagem da acentuação tônica da língua portuguesa - SILVA, Maria Luana Viana da (2020)
This thesis is connected to the research project "Game Based Teaching and Learning method in the Portuguese Language" (UFPA-Campus Castanhal) and it approaches the method about the construction of playful instruments and how it can be useful for teaching the Portuguese Language. Thusly, we used as a theoretical basis the assumptions of Almeida (2003, 2007), Bechara (2017), Cunha (2017), Fortuna (2011), Luckesi (2014), Kishimoto (2001), Lee (1997), Ney (2012), and others. In this sense, we have as overall objective the results of game based teaching and learning process in regard to the tonic accent of the Portuguese Language; and as specific objectives: 1) To formulate an educational game to assist in the teaching and learning process of tonic accent; 2) To substantiate that educational games can provide the learning of tonic accentuation in a useful way. As follows, our methodological procedures are based on a interpretative qualitative research based on the theorists: Gil (2006), Lüdke and André (1986) and Ohuschi (2006). With the results achieved, we highlight the fact that through the game based teaching it was possible a easier way to learn the tonic accent, in addition to a pleasant and useful interaction.